2012
DOI: 10.3892/etm.2012.688
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma treatment by uterine artery embolization using gelatin sponge prepared by the pumping method

Abstract: Uterine leiomyoma, a benign tumor, may be treated with drugs, albeit surgical resection is more common. The present study aimed to evaluate the treatment of leiomyoma cases by uterine artery embolization (UAE) using a gelatin sponge prepared by the pumping method. The results of 700 leiomyoma cases treated by UAE in the outpatient department were evaluated. UAE was performed by injecting gelatin sponge prepared by the pumping method into the uterine artery. Among 700 cases, effective cases were 680 (97.2%), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Transabdominal color Doppler ultrasonography ( Figure 1A) and dynamic computed tomography confirmed two extravasations into the uterine cavity originating from the right and left uterine arteries, respectively ( Figure 1B). We then performed UAE into the bilateral uterine arteries using an absorbable gelatin sponge (Serescue, Nippon Kayaku Co., Ltd., Tokyo, Japan) prepared by the pumping method, 5,6) and the extravasation disappeared. We began transfusion before performing UAE, and a total of 4 units of red cell concentrate and 4 units of fresh frozen plasma were transfused until just before the UAE.…”
Section: Case Reportmentioning
confidence: 99%
“…Transabdominal color Doppler ultrasonography ( Figure 1A) and dynamic computed tomography confirmed two extravasations into the uterine cavity originating from the right and left uterine arteries, respectively ( Figure 1B). We then performed UAE into the bilateral uterine arteries using an absorbable gelatin sponge (Serescue, Nippon Kayaku Co., Ltd., Tokyo, Japan) prepared by the pumping method, 5,6) and the extravasation disappeared. We began transfusion before performing UAE, and a total of 4 units of red cell concentrate and 4 units of fresh frozen plasma were transfused until just before the UAE.…”
Section: Case Reportmentioning
confidence: 99%
“…Embolization is performed using a gelatin sponge (Spongel; Astellas, Tokyo, Japan), and the embolic agent is created using the pumping or cutting method. In the pumping method [13], the water-soaked gelatin sponge is compressed into a syringe from which air is evacuated, and another syringe containing the contrast agent is connected via a T-shaped stopcock to the gelatin-containing syringe; subsequently, the gelatin sponge is crushed by alternately pumping 2 two syringes approximately 5 times. In the cutting method, the gelatin sponge, which is provided in the form of a sheet, is cut into approximately 1-mm cubes with a scalpel and scissors [14,15].…”
Section: Uae Protocolmentioning
confidence: 99%
“… 7 However, in Japan, these embolic agents were not commercially available until 2014, and gelatin sponge particles cut from sheets or porous gelatin particle (PGP), a roughly calibrated embolic agent made of gelatin sponge, have been used for UAE. 8 While several articles have shown that the outcomes of UAE using gelatin sponge were comparable to those of UAE using other embolic agents, 8 10 these reports were single-institutional studies, and further accumulation of clinical evidence is warranted. With this in mind, we retrospectively analyzed our 10-year experience of UAE with gelatin sponge particles and PGP and assessed the long-term clinical outcomes alongside a literature review.…”
Section: Introductionmentioning
confidence: 99%